Kualitas Semen Kambing Peranakan Boer - M. Hartono (Jurnal Penelitian Pertanian Terapan, 2010)
The research was aimed to study quality of semen crossbreed Boer goat. The study was conducted at Batu Kramat Village, Kota Agung Timur Subdistrict, Tanggamus District, Lampung Province during November-December 2008. A Completely Randomized Design with five replications was used with four breeds goat that were Kacang, PE, Boercang, and Boerawa. The result showed that breed of goat were not significantly different (P>0,05) about volume, concentration, and abnormality of semen, but were significantly affected (P<0,01) with motility and live-cells. The best quality of semen was Boerawa goat i.e. volume 1,02 ml; motility 88%; concentration 2.290.000.000 cells.ml-1; live-cell 89,67%; and abnormality 1,98%. Key word : quality of semen, crossbreed Boer goat